2015
DOI: 10.1038/sc.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting resilience in people with spinal cord injury during transition from inpatient rehabilitation to the community

Abstract: Study Design: This is a longitudinal design study. Objectives: The objective of this study was to determine factors that predict resilience in people with spinal cord injury (SCI) at discharge from inpatient rehabilitation and after reintegration into the community 6 months post discharge. Setting: This study was conducted in SCI rehabilitation units and the community in New South Wales, Australia. Methods: Participants included 88 adults with SCI admitted over almost 3 years into three SCI Units in Sydney. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 23 publications
3
64
2
3
Order By: Relevance
“…However, a stepwise approach whereby the clients and rehabilitation team identify small goals and steps to achieve enable the various threads of daily activities to be entwined while simultaneously increasing motivation, a sense of achievement and independence. Continuous reinforcement of the individual's capabilities build self‐efficacy (Craig et al., ) and in turn resilience among SCI survivors (Berry, Elliott, & Rivera, ; Driver et al., ; Guest, Craig, Tran, & Middleton, ). Importantly, self‐efficacy and resilience are acknowledged factors influencing rehabilitation outcomes following SCI (Middleton, Tate, & Geraghty, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a stepwise approach whereby the clients and rehabilitation team identify small goals and steps to achieve enable the various threads of daily activities to be entwined while simultaneously increasing motivation, a sense of achievement and independence. Continuous reinforcement of the individual's capabilities build self‐efficacy (Craig et al., ) and in turn resilience among SCI survivors (Berry, Elliott, & Rivera, ; Driver et al., ; Guest, Craig, Tran, & Middleton, ). Importantly, self‐efficacy and resilience are acknowledged factors influencing rehabilitation outcomes following SCI (Middleton, Tate, & Geraghty, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, people with high levels of self-efficacy and social support and low levels of catastrophization are associated with a low risk of psychological disturbance. Poor self-efficacy is associated with an increased risk of psychological disorders in those who sustain a SCI (Craig et al, 2015). In a cross-sectional survey which examined factors that contribute to the process of positive adjustment, or resilience, in a community sample of SCI survivors, 58% of the 60 respondents reported moderate to high levels of resilience and resilience correlated significantly with high self-efficacy with self-efficacy contributing to resilient behaviour (Kilic et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study employing a convenience population found that self-efficacy was positively correlated with resilience while in hospital and at 3 months post-SCI, and that levels of self-efficacy predicted levels of resilience while in hospital 21. Similarly, self-efficacy, as well as low levels of depressed mood, predict resilience in individuals with SCI at discharge and 6 months postdischarge from an inpatient rehabilitation setting into the community 22. It has been recommended that rehabilitation strategies enhance self-efficacy by strengthening the relationship between behaviors and perceived goals through increased self-monitoring and self-awareness 4…”
Section: Introductionmentioning
confidence: 99%
“…People with better physical capacity indicators are more active in daily and community life, better manage self-control mechanisms, and feel more emotionally stable [24,25]. According to authors [26,27], it is important during the inpatient rehabilitation program to promote physically active lifestyle and activities in daily life as well as to increase motivation to engage in vigorous physical activity not only during exercise, training or active leisure, but also during household activities.…”
mentioning
confidence: 99%